Nível de relação entre a assimetria dinâmica do centro de massa e a eficiência mecânica na corrida de 10km - Camila Cristina Melo (2018)
The first aim of this study was to analyze whether the level of asymmetry and mechanical efficiency would change over a long-distance running. The second aim was to investigate the relationship between the dynamic asymmetry of the center of mass and the mechanical efficiency of a 10-km running in a treadmill. Thirteen amateur runners (8 men and 5 women) were equipped with a triaxial accelerometer (fixed at the first sacral vertebra) and a portable gas analyzer mask and ran 10 km on a treadmill at a constant pre-determined velocity. The dynamic asymmetry of the center of mass in the vertical, anteroposterior and mediolateral axes were calculated, as well as the Global Symmetry Index. Running mechanical efficiency was calculated as the ratio between external work and the energy spent. The repeated measures ANOVA showed significant decreases of the Global Symmetry Index (p = 0,0001) and the running mechanical efficiency (p = 0,0001) over the 10 km. There was a significant moderate relationship between the Global Symmetry Index and running mechanical efficiency (r = 0,657, p = 0,015). The decrease in the vertical axis Symmetry Index showed a more significant contribution in decreasing the Global Symmetry Index than the symmetry of the other two axes. The increase in asymmetry explained 43,1% of the reduction in running mechanical efficiency over the 10-km run at a constant velocity. In conclusion, the dynamic asymmetry of the center of mass measured with an accelerometer is related to the running mechanical efficiency of amateur runners over a 10-km run. Although muscular fatigue has not been directly measured, it seems to be the main cause of the reduction in the Global Symmetry Index and in the running mechanical efficiency over a 10-km run.